Penerapan Model Pembelajaran Problem Based Learning Dengan Menggunakan Strategi Snowball Throwing Untuk Meningkatkan Hasil Belajar Ekonomi Pada Siswa Kelas XISma Negeri 2 Sukoharjo Tahun 2016 - Dwi Ningtyas, Retno, Dr.Djalal Fuadi.M.M (2016)
The purpose of this study was to determine student learning outcomes through learning model of problem-based learning (PBL) with learning strategies snowball throwing. This type of research is the PTK (Classroom Action Research) done in two cycles. Subjects were students of class XI IPS 1 SMA N 2 Sukoharjo totaling 36 students. Data collection methods used were interviews, observation, testing, field notes, documentation. Data were analyzed using reduction, presentation, verification of data and draw conclusions. The results of this study showed an increase in economic learning outcomes, can be seen from the average value of pre-cycle (initial value) is only 76.64. In the first cycle and the second cycle has risen 78.44 and 79.17, with an increase of pre-cycle to the first cycle of 2.36%, while the first cycle to the second cycle of 0.92%, so we can say the application of problem based learning models (PBL) and throwing snowball learning strategies proven to improve student learning outcomes in class XI IPS SMA N 2 Sukoharjo first semester of 2016.